Measuring the growth rate of structure around cosmic voids. Issue Volume 11:Issue S308(2015) (12th October 2016) - Hawken, A. J.; Michelett, D.; Granett, B.; Iovino, A.; Guzzo, L.
Abstract: Using an algorithm based on searching for empty spheres we identified 245 voids in the VIMOS Public Extragalactic Redshift Survey (VIPERS). We show how by modelling the anisotropic void-galaxy cross correlation function we can probe the growth rate of structure.